Lupus nephritis with massive subendothelial deposits in a patient with autoimmune hepatitis-related cirrhosis - Natsuki Shima; Keiichi Sumida; Hiroki Mizuno; Toshiharu Ueno; Masahiro Kawada; Akinari Sekine; Masayuki Yamanouchi; Rikako Hiramatsu; Noriko Hayami; Eiko Hasegawa; Tatsuya Suwabe; Junichi Hoshino; et al. (Human Pathology: Case Reports, 2018)
A 72-year-old Japanese woman with a history of autoimmune hepatitis-associated liver cirrhosis and portosystemic shunt was admitted to our hospital for evaluation of renal dysfunction, nephrotic range proteinuria, a high titer of anti-double-stranded DNA antibody, and hypocomplementemia. Renal biopsy showed massive subendothelial deposits (wire loop lesions), and class IV-G (A/C) lupus nephritis was diagnosed. Immunosuppressants, such as steroids (including intravenous methylprednisolone pulse therapy) and mycophenolate mofetil, could not prevent renal dysfunction. It was assumed that circulating immune deposits produced in the gastrointestinal tract entered the systemic circulation from the portal vein via the portosystemic shunt without hepatic clearance, resulting in massive subendothelial and mesangial accumulation compared to lupus nephritis patients without a shunt and causing renal injury. Keywords: Lupus nephritis, Systemic lupus erythematosus, Autoimmune hepatitis-associated liver cirrhosis, Portosystemic shunt, Wire loop lesion